استراتيجية شق الطرق الرومانية في مقاطعتي نوميديا وموريطانيا القيصرية من بداية العهد الامبراطوري إلى نهاية حكم الأسرة السيفيرية (27 ق. م – 235م) - رزوق نجاة (University Eloued جامعة الوادي, 2024)
الملخص: تناولت هذه الدراسة مرفقا مهما تمثل في الطرق، والتي أولاها الرومان أهمية كبرى نظرا لقيمتها العسكرية، والاقتصادية، ورسم لأجلها الأباطرة الرومان؛ من أغسطس إلى سيفيروس وخلفائه استراتيجية خاصة لخدمة أهدافهم الاستعمارية، وهذا ما تجلى من خلال سياستهم التي طبقوها في مقاطعتي نوميديا وموريطانيا القيصرية، فقد عمل هؤلاء الحكام على ربط أراضي هذه المقاطعات عن طريق شبكة هائلة من الطرق البرية، والتي برعوا في تنفيذها، فقد ربطوا جنوب مقاطعتي نوميديا وموريطانيا القيصرية بشمالها، عبر مجموعة من الطرق المهمة، منها طريق تيفست- هيبون، وطريق تيفست – لمبايسيس، في نوميديا، وطريق كويكول- سيتيفيس، أوزيا – رابيديوم، واستخدامها في الأغراض العسكرية، عن طريق تنقل عناصر الجيش الروماني بين المراكز العسكرية في الشمال والجنوب، والاقتصادية من أجل ربط المدن الاقتصادية الكبرى، مثل تيفست، وسيتيفيس، والأسواق التجارية، والأراضي الزراعية بمدن السواحل والموانئ الاستراتيجية لنقل المنتجات المختلفة إلى العاصمة روما. وبالتالي تحقيق الهدف العسكري الاستعماري الاستيطاني، ومن خلاله تحقيق الهدف الرئيسي ألا وهو الهدف الاقتصادي لاستنزاف ثروات المقاطعات المهزومة. Abstract: This study dealt with an important facility represented by the roads, which the Romans gave great importance to due to their military and economic value, and for which the Roman emperors; from Augustus to Severus and his successors drew up a special strategy to serve their colonial goals, and this was evident through their policy that they implemented in the provinces of Numidia and Mauretania Caesarea. These rulers worked to connect the lands of these provinces through a huge network of land roads, which they excelled in implementing. They connected the south of the provinces of Numidia and Mauretania Caesarea to its north, through a group of important roads, including the Thévest-Hippoon road, the Thévest-Lambaesis road in Numidia, and the Cuicul-Sitifis road, Ozia-Rapidium, and used them for military purposes, through the movement of Roman army elements between military centers in the north and south, and economic in order to connect major economic cities, such as Thévest, Sitifis, commercial markets, and agricultural lands with coastal cities and strategic ports to transport various products to the capital, Rome. Thus, achieving the colonial settlement military goal, and through it achieving the main goal, which is the economic goal of draining the wealth of the defeated provinces.
أطروحة دكتوراه
Keywords: الطرق الرومانية; الاستراتيجية; المعالم الميلية; نوميديا; موريطانيا القيصرية; الأهداف الاقتصادية; الأهداف العسكرية; Roman roads; strategy; Mile landmarks; Numidia; Caesarean Mauritania; economic goals; military goals.